Evaluasi kualitas pengukuran manajemen sistem tata kelola akademik menggunakan framework COBIT 2019 pada STIK Bina Husada - Mahardika, Billi; Sutabri, Tata; Cholil, Widya; Amin, Zaid (LPPM UNIVERSITAS BINA INSAN, 2024)
This study evaluates the effectiveness of the governance practices at STIK Bina Husada through the lens of COBIT 2019, aiming to identify critical process objectives and assess capability levels related to academic governance. The research problem centers on the alignment of institutional practices with established standards to enhance strategic management, innovation, and continuity. A mixed-methods approach was employed, utilizing questionnaires and activity analysis to evaluate the current capability levels of specific focus areas, namely APO02 (Managed Strategy), APO04 (Managed Innovation), and DSS04 (Managed Continuity). Participants included key stakeholders involved in the governance processes at STIK Bina Husada.The findings revealed that while APO02 achieved a capability level of 79.36% (largely achieved), it fell short of the desired fully achieved status. Conversely, APO04 demonstrated a capability of 100% at level one, indicating full achievement, but only a 68.12% capability at level two, which remains largely achieved. DSS04 also showed a similar pattern as APO04, with both objectives needing improvement to reach level three capabilities. The gap analysis highlighted a discrepancy of two levels between the current and desired capabilities for APO02, APO04, and DSS04.This evaluation marks the first comprehensive assessment of STIK Bina Husada's academic governance quality against the COBIT 2019 framework, emphasizing the need for continued improvement to meet strategic objectives. The implications of this research suggest that adopting structured frameworks like COBIT can significantly enhance management practices in academic settings.